2010
DOI: 10.1002/aoc.1711
|View full text |Cite
|
Sign up to set email alerts
|

Antituberculosis, antifungal and thermal activity of mixed ligand transition metal complexes

Abstract: Mixed-ligand complexes of the type [M(CQ)(Ph)(OH)(H 2 O)], where M = Cu(II), Ni(II), Co(II) and Mn(II), have been investigated. Furthermore, there has been some additional work investigating the effect of metal ions on biological activity. Aiming to obtain novel transition metal complexes that exhibit biological activity, we have synthesized mixed ligand complexes using clioquinol (5-chloro-7-iodo-8-hydroxyquinoline) and 1,10-phenanthroline as ligands. The compounds were characterized using IR, FAB mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…In fact, more than 200 8HQ-like compounds were identified to have an inhibitory effect against replicating TB 112. Results showed that 8HQ itself exerted the most potent activity among other compounds in its class 113. 8HQ can kill both replicating and nonreplicating TB in vitro, with a more potent effect noted for the nonreplicating type 109.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, more than 200 8HQ-like compounds were identified to have an inhibitory effect against replicating TB 112. Results showed that 8HQ itself exerted the most potent activity among other compounds in its class 113. 8HQ can kill both replicating and nonreplicating TB in vitro, with a more potent effect noted for the nonreplicating type 109.…”
Section: Introductionmentioning
confidence: 99%
“…The antitubercular activity of CQ-metal complexes were also reported 113. In particular, a series of mixed ligand metal complexes using CQ and 1,10-phenanthroline as ligands to coordinate with transition metal ions were synthesized and tested for antitubercular and antifungal activities 113.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal behaviors of the obtained complexes were also investigated. The thermal analysis techniques, such as thermogravimetry (TG), differential thermal analysis (DTA), and differential scanning calorimetry (DSC), were widely applied in studying the thermal behavior and the structure of metal complexes [14][15][16][17][18][19][20][21][22][23][24][25]. The results allowed us to acquire information concerning the structure of these compounds, including their thermal behavior and decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…[2] It was not until recently that stacking involving metal chelate rings has been recognized as an important factor influencing the crystal structure of metal-organic compounds; on this point, the copper(II)-carboxylate complexes with suitable Nheterocyclic auxiliary ligands are of interesting because the metal-N-heterocyclic chelate ring could exhibit some degree of "metalloaromaticity." [3][4][5][6][7][8][9][10][11][12][13][14][15] This classic concept was proposed a long time ago and it was recently reviewed and improved by H. Masui. [16,17] The increasing interest in this subject arises from its usefulness as a unifying approach for the reactivity, magnetic, spectral properties, and structure of so-called "metalloaromatic compounds."…”
Section: Introductionmentioning
confidence: 99%